SIRT2 directs the replication stress response through CDK9 deacetylation - Zhang, Hui (National Academy of Sciences, 2013)
Sirtuin 2 (SIRT2) is a sirtuin family deacetylase that directs acetylome signaling, protects genome integrity, and is a murine tumor suppressor. We show that SIRT2 directs replication stress responses by regulating the activity of cyclin-dependent kinase 9 (CDK9), a protein required for recovery from replication arrest. SIRT2 deficiency results in replication stress sensitivity, impairment in recovery from replication arrest, spontaneous accumulation of replication protein A to foci and chromatin, and a G2/M checkpoint deficit. SIRT2 interacts with and deacetylates CDK9 at lysine 48 in response to replication stress in a manner that is partially dependent on ataxia telangiectasia and Rad3 related (ATR) but not cyclin T or K, thereby stimulating CDK9 kinase activity and promoting recovery from replication arrest. Moreover, wild-type, but not acetylated CDK9, alleviates the replication stress response impairment of SIRT2 deficiency. Collectively, our results define a function for SIRT2 in regulating checkpoint pathways that respond to replication stress through deacetylation of CDK9, providing insight into how SIRT2 maintains genome integrity and a unique mechanism by which SIRT2 may function, at least in part, as a tumor suppressor protein.